Analysis on shari'ah governance structure of Islamic banking and finance in Malaysia, Indonesia and Kuwait - Izyan Farhana binti Zulkarnain (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2014)
Shari'ah board plays an essential role in shari'ah governance structure of Islamic banking and finance. This board is responsible to ensure that Islamic financial activities are shari'ah compliant. Basically, in establishing shari'ah governance structure, several approaches are identified to be adopted by different countries which include the centralised approach, self-regulatory approach and other approaches. However, this research will be focusing only on Malaysia, Indonesia and Kuwait which adopted the centralised approach in developing their shari'ah governance structure. The importance of shari'ah governance and its implementation in these three countries are also explored and discussed by the researcher. Malaysia requires the establishment of Shariah Advisory Council and Shariah Committee under the supervision of the Central Bank of Malaysia. On the other hand, the National Shariah Board in Indonesia is a non-government organisation which issues fatwa on shari'ah matters and the Sharia Supervisory Board is the term used for those scholars who are appointed in Islamic financial institutions. As for Kuwait, the final authority in deciding on matters relating to Islamic financial business is vested upon the Fatwa Board in the Ministry of Awqaf and Islamic Affairs which is a separate entity from the Central Bank of Kuwait. However, the Shariah Supervisory Board in Islamic banks is governed by the Central Bank of Kuwait. The research concluded that the shari'ah board is indeed significant to establish good shari'ah governance in Islamic financial institutions by practising shari'ah compliant activities in accordance with the shari'ah.